Sensing the World: Social Sensorium in the Chemical Use of Selected Youth in the Philippines - Dalisay, Soledad Natalia M. (Social Science Diliman: A Philippine Journal of Society and Change, 2015)
This study uses the interpretive approach in looking into the everyday chemical use of the youth in a port city of the Philippines. It is an attempt at “sensing the world,” of these youth. Herein, the senses become the “lens” through which their social lives could be understood. This study explored the youth’s sensorial experience from chemical use and hopes to provide the reader a glimpse of such chemical sensorium. Keywords: Anthropology of the senses, chemical use, Philippines, youth, sociality of chemical use